Last mile delivery: service diversity or standardization: Nespresso’s case study - Santos, João Pedro Xavier dos (2023)
The increasing necessity to create convenience for the consumer has been a challenge for all companies that invest in e-commerce. Besides the complexity of creating convenience, there is also the need to make these processes as efficient as possible. The last mile is the most expensive part of the supply chain and for that reason it is important to create an effort to reduce costs without ever neglecting the quality of the service. Nespresso has the challenge of delivering in the most prestigious way possible (given the strategic position of the brand), but at the same time to keep the operation efficient and as cheap as possible. This thesis therefore studies the impacts that the lack of scale creates in Nespresso's supply chain. In order to understand these impacts, two perspectives were analyzed. The impacts that this strategy has for the company's operations and the impacts it has for the brand's consumer. To this end, interviews were conducted with employees linked to the supply chain area, focus groups with consumers and also an interview with a professional in the logistics area who is also a Nespresso customer ambassador. This analysis allowed us to identify that the brand has a distinctive position in the market and that it operates in a totally different way from its competitors. For this reason it is expected that they deliver in more ways, even if these make the operation more expensive and less profitable. On the other hand it could be important to re-analyse the possible merger of some delivery methods or simply their reformulation. Furthermore it also allowed us to draw conclusions for other markets and companies and to understand the real importance that scale plays in last mile efficiency.